Cognitive Behavior Group Counseling to Reduce Academic Anxiety (Universitas Negeri Semarang, 2019)
This study attempted to examine the effectiveness of cognitive behavior group counseling with cognitive restructuring technique to reduce academic anxiety. Meanwhile, the design used in this study was pre-test and multiple post-test designs. In this case, the researchers involved eight students in the eleventh grade or class XI of Public Senior High School 1 Pringgarata (SMA Negeri 1 Pringgarata). The subjects’ data were collected through statistic Achievement Emotions Questionnaire (AEQ) which was focused on class related anxiety, learning related anxiety, and text anxiety. For more, the collected data were analyzed by using repeated measure ANOVA. It resulted that there was a reduction in students’ academic anxiety (F(2.14) = 393.24, p < 0.01). These findings assert that cognitive behavior group counseling with cognitive restructuring technique is effective to reduce the academic anxiety of the students of SMA Negeri 1 Pringgarata.